Training intensity distribution of young elite soccer players - Oliveira Borges, T.; Moreira, A.; Thiengo, C. R.; Silva Duarte Medrado, R. G.; Titton, A.; Rodrigues Lima, M.; Nunes Martins, A.; Saldanha Aoki, M. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2019)
The current study described the training load and intensity distribution of 30 elite Under 20 soccer players (17.9 ± 0.6 years, 180.3 ± 5.7 cm, 73.7 ± 8.8kg) from a 3-time FIFA Club World Cup champion. Session-rating of perceived exertion (s-RPE), internal training load (ITL) and monotony were recorded across 40 training sessions. Mixed-effects modeling was used for data analysis. The athletes performed 33.0 ± 6.9 out of 40 planned training sessions. Most common reasons for absence from training included sickness or minor injuries. Overall, these training sessions summed 2928.7 ± 627.6 minutes. Athletes performed significantly more training sessions at low and moderate intensity zones than at high-intensity zone (p <0.0001). The current data indicate that elite young soccer players perform their training sessions predominantly at the low-intensity zone. Training monitoring is an important aspect of the sport training process evolution. In fact, previous evidencehas already shown that an appropriate intensity distribution preventsmaladaptation from sports training and may optimize athletic performance. Therefore, coaches should implement strategies to monitor training loads during pre-season and competitive periods.